Quality of donkey bresaola - Agostino Sevi (Italian Journal of Animal Science, 2010)
Nutritional and organoleptic properties were evaluated in bresaola of cow and don- key meat and, moreover, was made a comparison between these two products. The cured products were made from semitendinosus muscle taken from 8 female donkeys and 8 cows. Donkey bresaola showed lower SFA percentage (P<0.05) and higher PUFA content (P<0.01) with higher fatty acids ω 3 (P<0.01) than beef bresaola. Donkey bresaola showed higher content of protein (P<0.01) and essential amminoacids (P<0.05) than beef bresaola. No differences were found for sensorial properties. Our in- vestigation demonstrates the possibility of trasforming donkey meat into a product similar to that of beef with a high nutritional value.